Histomorphological alterations in uterus of repeat breeding cows with subclinical endometritis following E. coli lipopolysaccharide and autologous serum therapy - SINGH, JAGIR; SINGLA, P; DHALIWAL, G S; KUMAR, AJEET; BANGA, H S (The Indian Journal of Animal Sciences, 2011)
Studies were conducted in 36 repeat breeding crossbred cows to diagnose different degrees of subclinical endometritis through uterine histopathology and to investigate the effects of intrauterine infusion of 100 μg of E. coli lipopolysaccharide (LPS) or its combination with autologous serum (5 ml) 12 h post AI on conception rates. Histopathology of endometrium revealed mild endometritis in 30 cows as indicated by mild to moderate infiltration of neutrophils, mononuclear cells, congestion of blood vessels, haemorrhage and oedema in lamina propria. Mild chronic endometritis (n=5) exhibited desquamation in the endometrium along with mild subepithelial infiltration of mononuclear cells and its periglandular aggregation. Chronic endometritis (n=1) was identified by infiltration of mononuclear cells, marked fibroplasia, rarification of endometrial glands or even its replacement. Mild to severe infiltration of neutrophils along with few healthy epithelial cells was observed in uterine lumen following the treatment. Polymorphonuclear cells in uterine flushings were significantly higher in LPS + autologous serum treated as compared to LPS treated cows. Maximum cows (91.67%) conceived with the treatment of LPS and its combination with autologous serum followed by LPS (75%). It was concluded that different degrees of subclinical endometritis could be diagnosed through histopathological examination of endometrium and fertility could be improved following intrauterine infusion of LPS and/or its combination with autologous serum by enhancing the nonspecific uterine immunity.